2022
DOI: 10.3390/mi13040586
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Logic and Genetic-Based Algorithm for a Servo Control System

Abstract: Performing control is necessary for processes where a variable needs to be regulated. Even though conventional techniques are widely preferred for their implementation, they present limitations in systems in which the parameters vary over time, which is why methods that use artificial intelligence algorithms have been developed to improve the results given by the controller. This work focuses on implementing a position controller based on fuzzy logic in a real platform that consists of the base of a 3D printer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…They enable us to describe these kinds of scenarios mathematically and then arrive at decisions according to the information provided. In numerous applications, such as artificial intelligence [19], decision-making [20][21][22], and control systems [23][24], fuzzy subsets are utilized. By making encryption unpredictable, fuzzy logic increases cryptographic system security.…”
Section: B Fuzzy Logic Role In Cryptographymentioning
confidence: 99%
“…They enable us to describe these kinds of scenarios mathematically and then arrive at decisions according to the information provided. In numerous applications, such as artificial intelligence [19], decision-making [20][21][22], and control systems [23][24], fuzzy subsets are utilized. By making encryption unpredictable, fuzzy logic increases cryptographic system security.…”
Section: B Fuzzy Logic Role In Cryptographymentioning
confidence: 99%
“…Because of the recent relevant works in the area, it was observed that there were developments for controllers based on artificial intelligence techniques. Thus, the authors of this paper have proposed the development of a fuzzy controller for pressure control in a water supply network, considering the good performance of fuzzy control applied in nonlinear systems found in the literature [ 17 , 18 , 19 ].…”
Section: Related Workmentioning
confidence: 99%
“…For instance, [20] implemented a GA for online self-tuning with a focus on high-quality servo control and reduction of vibrations while positioning a linear motion system. [21] uses GA to optimize the values of the membership functions in the fuzzification of the input variables to a fuzzy controller in a servo system. The work presented in [22] used a GA to find the optimal flyable path for the UAVs in a 3D environment.…”
Section: Introductionmentioning
confidence: 99%